Marcel Broodthaers and Film: A Second of Eternity - Chesher, Andrew; de Bruyn, Eric C. H; García Bardón, Xavier; Friling, Charlotte; Jenkins, Bruce; Schultz, Deborah; Wall-Romana, Christophe (Leuven University Press, 2024)
Broodthaers' oeuvre and the history of experimental film. Marcel Broodthaers, one of the key figures of the postwar avant-garde, has been recognized and extensively studied as a poet who became a visual artist in 1964. However, years before creating his first sculptural objects and installations, Broodthaers made his debut as a filmmaker in 1957 with La Clef de l’horloge, embarking on a prolific cinema practice that yielded more than fifty films shot on 35mm and 16mm. Cinema, both as a medium and principle, was crucial to his artistry. Broodthaers's writings and visual oeuvre are permeated with allusions to film, its history, and its technology. Covering both well-known titles such as Le Corbeau et le renard (1967), La Pluie (1969), and Une Seconde d’éternité (1970) as well as many lesser-known Broodthaers films, the essays in this book discuss his films as inseparable from his entire oeuvre while situating them in the larger history of experimental film. In addition, the book scrutinizes his experiments with cinepoetry and expanded cinema, as well as his interest in early cinema and his fascination with signs and inscriptions. Marcel Broodthaers and Film brings together essays by Andrew Chesher, Eric C. H. de Bruyn, Xavier García Bardón, Charlotte Friling, Steven Jacobs, Bruce Jenkins, Deborah Schultz, Christophe Wall-Romana, and Raf Wollaert.